משה גושךנוטשטין, הלשון העברית והלשונות השמיות. קווים למבוא Hebrew and Semitic Languages. An Outline Introduction - Goshen-Gottstein, Moshe H. (1965)
all articles are taken from the “Lexicon Biblicum” edited by N. Solieli and M. Berkooz. Tel-Aviv 1965. Dvir; spez. 18-28 שפות שמיות (Einteilung der semitischen Sprachen).